Dinamika Psikologis Pasangan Suami Istri yang Belum Memiliki Anak - Hermi Pasmawati (Institut Agama Islam Negeri Kerinci, Indonesia, 2019)
Children are a gift and at the same time trust from Allah SWT. After marriage one of the things that awaited by the couple is the presence of a baby in the middle of the family, but not a few phenomena in the field of couples who have not been blessed with children, this condition causes feelings of anxiety, because of the demands of the couple or family of the couple and comparison with other couples who have have children, this condition certainly provides its own psychological effects for couples. Based on this phenomenon, there are two problems examined in this paper, namely; 1) What is the psychological dynamics of a married couple who do not have children, 2). How are the efforts made by married couples in overcoming psychological problems. This type of research used in this research is descriptive qualitative with a case study approach. There were ten informants in the study, consisting of six husband and wife couples who did not have children and four supporting informants. The results found that (1) psychological dynamics that occur in married couples who do not have children in East Kikim sub-district, viewed from the emotional aspects of changing at the beginning of marriage, husband and wife do not feel there is a burden, but with increasing age of marriage and not yet blessed with children, making them feel anxious and worried, even because they have been married for decades and still do not have children, so they surrender. Seen from the aspect of adjustment, there are several couples in interacting with the family environment, neighbors or the community does not experience difficulties, but there are also those who experience difficulties in adjusting. Viewed from the aspect of motivation there are some couples who get support and advice from family and neighbors, but there are also those who only support each other between the husband and wife. positive activities such as religious activities, convince yourself that this condition can certainly be bypassed and then do activities that you like, while also doing medical or herbal treatment